The Clinical Characteristics of Patients With Nonneutropenic Invasive Pulmonary Aspergillosis - Liu, Lulu; Gu, Yu; Wang, Yu; Shen, Kunlu; Su, Xin (Frontiers in Medicine, 2021)
Objective The goal of this study was to reveal the clinical manifestations of nonneutropenic invasive pulmonary aspergillosis (IPA), which are different from those of neutropenic patients. Methods The clinical data of patients with nonneutropenic IPA were collected in the Department of Respiratory and Critical Care Medicine, Jinling Hospital, from February 2009 to November 2019. We analyzed the general conditions, clinical manifestations, imaging findings and laboratory tests of these IPA patients. Results A total of 116 patients with nonneutropenic IPA (31 proven and 85 probable) were included. They had an average age of 59.8 years. The most common underlying disease was chronic obstructive pulmonary disease (COPD, n=33). The common clinical symptoms included cough (93.1%, n=108), expectoration (59.5%, n=69), fever (57.8%, n=67), hemoptysis (30.2%, n=35), and dyspnea (40.5%, n=47). The common CT imaging manifestations included consolidation (47.4%, n=55), cavities (47.4%, n=55), air crescent sign (14.7%, n=17) and nodules (8.6%, n=10). Multiple lesions (74.1%, n=86) were more common than single lesions (17.2%, n=20) and diffuse lesions (8.6%, n=10). The positive rate of laboratory tests was 88.2% (30/34) for BALF galactomannan (GM), 55.4% (56/101) for serum GM, 45.3% (48/106) for BDG, 43.3% (46/106) for sputum culture and 36.4% (20/55) for BALF culture. Patients had high serum GM level (GM optical density index (ODI) >1) were more likely to have severe respiratory symptoms and higher serum ferritin. Further investigation showed that there was a positive correlation between serum GM level and serum ferritin level. Conclusion The clinical symptoms and radiological manifestations of nonneutropenic IPA are diverse and often lead to delayed diagnosis. It is important to become more vigilant of aspergillosis in nonneutropenic patients in order to achieve early diagnosis and treatment, and to reduce mortality.